Billy T. James - te thesis : comedy, hybridity & mimicry in post-colonial Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts, in English at Massey University, Wellington (via distance), Aotearoa New Zealand - Burgess, Daniel (Massey University, 2023)
Even decades after his passing in 1991, Billy T. James is a comedy icon of Aotearoa New Zealand (NZ). However, James was more than just an entertainer. He was a prominent and popular Māori figure in an era when colonial history and race-relations were brought to the fore, and the country was revisiting its identity as a colonial and postcolonial nation. By analysing a variety of examples from James’ comedy with close reference to biographical details, popular comedy, scholarly literature, and sociological, historical, and post-colonial contexts, I investigate how James was able to work both with and against the coloniser (Pākehā). Drawing on Homi K. Bhabha’s postcolonial theories of “Third Space”, hybridity and mimicry (see chapter three), I situate James as a comic hybrid—who drew on distinct aspects of te ao Māori (see chapter one) and broader Western comedy conventions (see chapter two)—and a colonial mimic—who used his comedy as a constructive comic treatment of race and culture (see chapter four). Yet, the understanding of James’ comic treatment of race and culture in its postcolonial context must also contend with the numerous possible interpretations of racial humour, which range from offence to the direct enjoyment of stereotyped material. To navigate these interpretations, I employ Dustin Goltz’s discussion of ‘intent, context, and audience response’ of controversial humour to understand how James’ potentially offensive comic treatment of Māori can be sufficiently debated through the concept of ‘ironic performativity,’ and how the plausible audience interpretations of James’ comedy can be read in a more careful way. Accordingly, through the intertwining of textual analysis and a critical engagement with broader contexts and academic literature, I thus position James’ comic hybridity and mimicry as a social critique of racism and colonial history, whereby he became a necessary arbiter of debate in post-colonial Aotearoa NZ.
Keywords: 360403 Drama, theatre and performance studies; 470213 Postcolonial studies